1999
DOI: 10.1177/204748739900600604
|View full text |Cite
|
Sign up to set email alerts
|

Job Control, Job Demands and Social Support at Work in Relation to Cardiovascular Risk Factors in MONICA 1995, Göteborg

Abstract: Background Job control and work environment are related to risk of coronary heart disease (CHO), but there is limited understanding of the independent risks associated with these factors.Objective To investigate the association between psychosocial work characteristics and biological risk factors for both sexes for a random population sample in Goteborq, Sweden.Design A cross-sectional study.Methods We used an age-stratified random sample of men and women aged 25-64 years comprising 1200 men and 1412 women, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 28 publications
5
70
1
Order By: Relevance
“…10 With male workers, Netterstrøm et al 11 showed a significant association between BMI and job strain. In contrast, Kornitzer and Kittel, 12 Steptoe et al 13 and Jönsson et al 14 did not find significant associations between BMI and psychological job stress in men. Thus, earlier findings about the relationship between obesity and job stress were inconsistent.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…10 With male workers, Netterstrøm et al 11 showed a significant association between BMI and job strain. In contrast, Kornitzer and Kittel, 12 Steptoe et al 13 and Jönsson et al 14 did not find significant associations between BMI and psychological job stress in men. Thus, earlier findings about the relationship between obesity and job stress were inconsistent.…”
Section: Introductionmentioning
confidence: 81%
“…The questions have a total of 17 items to measure job stress factors of psychological workload (Table 1). These are categorized as quantitative workload (1-3), qualitative workload (4-6), physical workload (7), job latitude (8-10), application of technology (11), interpersonal conflict (12)(13)(14), workplace environment (15), and appropriateness of work (16,17). The section on psychological stress response (Table 2) has a total of 18 items to measure positive responses (activity (1-3)) and negative responses (anger (4-6), fatigue (7)(8)(9), tension/anxiety (10)(11)(12), and depression (13)(14)(15)(16)(17)(18)).…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 While some studies have found an association between high strain, 6,7 high demands, 6,8,9 low control, 3,10 and increased BMI, other studies have reported no associations between these psychosocial characteristics of the work environment and BMI, [11][12][13][14] and, in some samples, high strain or low control were associated with lower BMI. 15,16 Associations of job strain and its components with BMI have been found to vary by sex, but not in a consistent manner 17 and stress has also been proposed to be linked with BMI beyond the work context.…”
Section: Introductionmentioning
confidence: 94%
“…This might explain, in part, the mechanism underpinning the interactive effects proposed by Kivimäki et al (J Occup Health 2010; 52: 66-73) Key words: Body mass index, Hyperphagia, Obesity, Psychological stress When stressed, some people lose and other people gain weight 1) . Although some studies have found associations between stressful work environments and increased body mass index (BMI) [2][3][4][5][6][7] , others have reported no associations between these variables [8][9][10][11][12][13] . Moreover, a highly stressful work environment was associated with low BMIs in several samples 14,15) .…”
mentioning
confidence: 99%